Gamification and repurchase intention among Shopee users in Cirebon: the mediating role of positive emotion - Ayu Sulastri; Siska Ernawati Fatimah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effect of gamification on repurchase intention, the effect of gamification on positive emotion, the effect of positive emotion on repurchase intention, and the mediating role of positive emotion among Shopee users in Cirebon. This study employed a quantitative cross-sectional design. A total of 150 active Shopee users were selected through purposive sampling based on the criteria of having used Shopee gamification features and having made repeat purchases within the previous three months. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that gamification has a positive and significant effect on both positive emotion and repurchase intention. Positive emotion also has a positive and significant effect on repurchase intention. Furthermore, positive emotion significantly mediates the relationship between gamification and repurchase intention. These findings indicate that Shopee’s gamified features encourage repeat purchasing not only directly but also through the creation of positive emotional experiences. The study recommends that e-commerce platforms develop gamified features that not only increase user interaction but also strengthen emotional engagement to foster customer loyalty and repeat purchasing.